Faktor-Faktor Yang Mempengaruhi Kesediaan Petani Meremajakan Tanaman Kelapa Sawit di Desa Tebing Tinggi Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat - Wiwin Alawiyah; Heber Imun (Universitas Batangahari Jambi, 2022)
Palm oil is one of the plantation commodities that has received great attention in Indonesia because it has very high economic value as a producer of vegetable oil for food products, industrial oil, and biofuels. One of the important factors that determine the success of oil palm development activities is and from the farmers who participate in the replanting activities. Without the participation of farmers, replanting activities will not succeed because farmers are the main actors in the agricultural development program. The research aims to determine 1) the socio-economic conditions of farmers who are rejuvenating oil palm plants, 2) the factors that influence the willingness of farmers to rejuvenate oil palm plants. This research uses survey method. This research uses survey method. Research data collected is primary data collected directly from farmers. Data on farmer characteristics were analyzed descriptively, while the factors that determine farmers' willingness to rejuvenate oil palm plantations were analyzed using logistic regression models. The number of respondent farmers in the study as many as 50 people consisting of 64 percent of farmers stated that they were willing to carry out oil palm rejuvenation and 36 percent of farmers were not willing. Farmer's age, length of farming, plantation area and age of oil palm plants have a significant (significant) effect on the chances of farmers' willingness to replant oil palm plants in Tebing Tinggi Village, Tebing Tinggi District, Tanjung Jabung Barat Regency. Then the formal education of farmers and the number of dependents of the farmer's family have no significant (non-significant) effect on the chances of farmers' willingness to replant oil palm plants in Tebing Tinggi Village, Tebing Tinggi District, Tanjung Jabung Barat.